PERSEBARAN OPIUM DI INDONESIA BAGIAN TIMUR ABAD XIX - Nur anisa (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2018)
In the second half of the nineteenth century, the colonial authority turned 4 ports namelyMakassar, Ambon, Banda and Menado to become “free ports” while another, Timor-Kupang, an“international port.” In the same period, opium imported from Bengal, Manila, and areas in India,became one of the most sought after commodities in Southeast Asia and especially in the DucthIndies. This paper discusses the opium trade in the five ports in the eastern part of what is nowIndonesia, between 1850-1870. The export and import data show that opium was highly soughtafter like a primary commodities (such as rice and textile). The farming system for opium traderegulated by the colonial government was dominated by Chinese traders.